2019
DOI: 10.1186/s12936-019-2969-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of insecticides used in indoor residual spraying for malaria control: an experimental trial on various surfaces in a “test house”

Abstract: Background: Malaria is a public health problem in the Brazilian Amazon region. In integrated vector management for malaria (anopheline) control, indoor residual spraying (IRS) represents one of the main tools in the basic strategy applied in the Amazonian states. It is essential to understand the residual efficacy of insecticides on different surfaces to determine spray cycles, ensure their rational use, and prevent wastage. This study aimed to evaluate the residual efficacy of six insecticide formulations use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…Although there is some evidence to suggest that acypermethrin degrades in UV [47] other studies have shown that repeated exposure to UV did not reduce the e cacy of the Interceptor netting [48]. In addition, the surface on which the insecticide is applied plays a signi cant role in determining the effectiveness of the insecticide treatment [42,49,50]. In addition, although the present study did not evaluate this aspect, as the netting was placed on a plywood substrate, its e cacy could have been affected by either the possible exposure to fungal growth encouraged by the proximity to damp wood or the interaction between the l-cypermethrin and the constituents of the plywood.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is some evidence to suggest that acypermethrin degrades in UV [47] other studies have shown that repeated exposure to UV did not reduce the e cacy of the Interceptor netting [48]. In addition, the surface on which the insecticide is applied plays a signi cant role in determining the effectiveness of the insecticide treatment [42,49,50]. In addition, although the present study did not evaluate this aspect, as the netting was placed on a plywood substrate, its e cacy could have been affected by either the possible exposure to fungal growth encouraged by the proximity to damp wood or the interaction between the l-cypermethrin and the constituents of the plywood.…”
Section: Discussionmentioning
confidence: 99%
“…This product has a residual effect for 4 months requiring three annual applications [82]. In the Amazon, factors such as the operational cost of mobilizing teams to perform insecticide spraying, the difficulty in accessing remote areas at adequate frequency, the variability of dwellings, and variable environmental conditions, may compromise the efficacy of IRS [88]. In fact, few systematic evaluations on the impact these measures have on suppressing anopheline populations and reducing levels of malaria transmission in the Brazilian Amazon have been performed [82,88].…”
Section: Indoor Residual Spraying (Irs)mentioning
confidence: 99%
“…In the Amazon, factors such as the operational cost of mobilizing teams to perform insecticide spraying, the difficulty in accessing remote areas at adequate frequency, the variability of dwellings, and variable environmental conditions, may compromise the efficacy of IRS [88]. In fact, few systematic evaluations on the impact these measures have on suppressing anopheline populations and reducing levels of malaria transmission in the Brazilian Amazon have been performed [82,88]. While IRS is applicable and effective in urban and peri-urban environments, issues need to be addressed regarding gold miners who often live in huts without walls, continuously exposed to mosquito bites, unconventional indigenous house architecture that may not favor IRS and the lack of studies regarding the stability of insecticides applied on unconventional surfaces and under extreme humidity and temperature environmental conditions [89].…”
Section: Indoor Residual Spraying (Irs)mentioning
confidence: 99%
“…Several reports indicated consistent and correct utilization of ITNs, particularly the LLINs proven to reduce the transmission rate up to 90% [11][12][13]. IRS is also an extremely effective means of malaria control strategy when properly applied in areas where malaria is epidemic [10,14]. In Ethiopia following the WHO recommendation, ITNs have been distributed in all malarious areas free of charge via health workers, volunteers and local administrators.…”
Section: According To the Federal Ministry Of Health (Fmoh) National mentioning
confidence: 99%